Optimal treatment for penile verrucous carcinoma: a systematic literature review - Jo, Dong In (BMC Urol, 2021)
Verrucous carcinoma, a rare low-grade well-differentiated squamous cell carcinoma, is known for its favorable biological behavior and lack of metastatic potential. However, aggressive resection is problematic in terms of compromised function and aesthetics. Hence, more conservative treatments are needed. Methods: To identify the up-to-date general biological behavior, diagnosis, and treatment trends, we searched PubMed using the keyword “penile verrucous carcinoma” without restrictions on publication date. Results: Current treatments for penile verrucous carcinoma include wide surgical excision, seldom preventive lymphadenectomy, and conservative chemotherapy without surgery or local excision with safe margins. Despite the advent of partial penectomy to minimally impact function and aesthetics, affected patients experience psychosexual problems. Local excision can be used to save the penile shaft and glans penis without preventive lymphadenectomy or adjuvant therapy and can achieve good clinical prognosis with rare recurrence. Conclusions: To preserve the functional and cosmetic aspects, we recommend local excision, especially for tumors measuring < 3 cm and classified as stage T1 according to the 2016 tumor node metastasis clinical and pathological classification for penile cancer.